Exploring the relationship between super-leadership, self-leadership, and exercise commitment in university Taekwondo teams - Park, Myoung-eun; Byon, Kevin K. (Frontiers in Psychology, 2024)
Promoting super-leadership is crucial for the sustainable growth of college sports teams, especially as teams are experiencing a noticeable shift towards a more horizontal dynamic, where athletes themselves are emerging as leaders. However, there is a lack of research on the effectiveness of super-leadership and its possible outcomes in the context of collegiate Taekwondo teams. This study aims to investigate the impact of super-leadership on athletes' self-leadership and exercise commitment and examine the mediating role of self-leadership in this relationship among collegiate Taekwondo athletes in South Korea. A total of 147 survey data were analyzed by structural equation modeling. The findings revealed that superleadership was found to have a positive impact on both athletes' self-leadership (β=0.71, p<0.001) and exercise commitment (β=0.30, p<0.05). Additionally, the study reveals athletes' self-leadership significantly impacts exercise commitment (β=0.34, p<0.05). Our findings also demonstrate that self-leadership was identified as a partial mediator in the relationship between super-leadership and exercise commitment (∆χ²=4.46, p>.05). Theoretical and practical implications were discussed based on the current study's findings.